2008
DOI: 10.1007/s00726-008-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

l-Proline is a sedative regulator of acute stress in the brain of neonatal chicks

Abstract: The purpose of the present study was to clarify the central nervous system function of amino acids during acute stress. In Experiment 1, changes in free amino acid pattern were investigated in the brain of neonatal chicks exposed to either restraint with isolation-induced or fasting stress. L-proline and L-arginine were decreased in the telencephalon and diencephalon under any stress. Since the central nervous system functions of L-arginine during the stress response has recently been reported, in Experiment 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…It was the first time we evaluate the attenuate effect of dietary proline on environment stress in aquatic animals, similar studies have done in bacteria, plants, chicks, piglets and humans before (Hamasu et al, 2009;Lopez-Carrion et al, 2008;Madan et al, 1995;Phang et al, 2008a). The present and previous studies suggested that L-proline may have a critical role to attenuate stress response in a variety of species.…”
Section: Discussionsupporting
confidence: 50%
“…It was the first time we evaluate the attenuate effect of dietary proline on environment stress in aquatic animals, similar studies have done in bacteria, plants, chicks, piglets and humans before (Hamasu et al, 2009;Lopez-Carrion et al, 2008;Madan et al, 1995;Phang et al, 2008a). The present and previous studies suggested that L-proline may have a critical role to attenuate stress response in a variety of species.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, it is likely that these amino acids are involved in the sedative and/or hypnotic effects of glucose. On the other hand, other amino acids which have sedative effects in chicks, such as alanine (L-alanine in Kurauchi et al, 2006), asparagine (Lasparagine in Yamane et al, 2009b), ornithine (L-ornithine in Suenaga et al, 2008b), proline (L-proline in Hamasu et al, 2009), serine (L-serine in Asechi et al, 2006) and tryptophan (L-tryptophan in Yoshida et al, 2012), had no effects in the present study. The relationship among these amino acids and sedative effects of centrally injected glucose may be weak.…”
Section: Discussionmentioning
confidence: 41%
“…One of them is associated with non-essential amino acid synthesis, and some of these amino acids, such as L-glutamate, γ-amino butyric acid (GABA), glycine and so on, have crucial functions in major excitatory and inhibitory neurotransmission. In addition, some amino acids, such as L-serine, L-cysteine, glycine , L-alanine (Kurauchi et al, 2006), L-arginine (Suenaga et al, 2008a), L-ornithine (Suenaga et al, 2008b), β-alanine (Tomonaga et al, 2004) and L-proline (Hamasu et al, 2009), have sedative and/or hypnotic effects that can be induced by central injection in neonatal chicks under acute stressful conditions. On the other hand, metabotropic glutamate receptor subtype 1 (mGluR1), one of the glutamate receptors, is involved in long-term memory formation in the passive avoidance test in chicks (Baker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central administration of amino acids such as DLtryptophan (Kurauchi et al, 2006a), L-asparagine (Yamane et al, 2009b), L-proline (Hamasu et al, 2009a(Hamasu et al, , 2010, Lserine (Asechi et al, 2006), L-arginine (Suenaga et al, 2008a), L-ornithine (Suenaga et al, 2008b), L-aspartate (Yamane et al, 2009b;Erwan et al, 2012), L-glutamate (Yamane et al, 2009c), ß-alanine (Tomonaga et al, 2004), L-alanine (Kurauchi et al, 2006b), L-cysteine (Yamane et al, 2009a), GABA (Shigemi, Tomonaga and Furuse, unpublished data), glycine (Asechi et al, 2006), and L-serine-ophosphate (L-SOP) (Asechi et al, 2006) attenuate the stress response in neonatal chicks.…”
Section: Introductionmentioning
confidence: 99%